Cultural Tourism Research Methods - Richards, Greg (CABI, 2014)
This volume has its roots in the Cultural Tourism Research Project launched in 1991 by the Association for Tourism and Leisure Education (ATLAS). Over the years, this project has involved a large number of researchers from many countries around the globe in undertaking various forms of cultural tourism research. Details of these activities can be found on the website at http://www.tram-research.com/atlas. As outlined in this volume, much of the early research effort was directed at gathering empirical data on the profile of cultural tourists, their motivations and behaviour, mainly through survey research. Although this activity has greatly improved our knowledge of whatcultural tourists do, recent meetings of the ATLAS Cultural Tourism Research Group have identified a growing dissatisfaction with this more traditional quantitative approach. Critical members, in particular Esther Binkhorst, Marjan Melkert and Katleen Vos, all three of whom are contributors to this volume, therefore began to plead for a qualitative-oriented research philosophy as a breeding ground for methodological innovations which could enrich the field of cultural tourism studies with new insights and perspectives. In 2007 a call for papers was launched among both members of the group and the global cultural tourism research community, resulting in the chapters collected in the current volume. The intention was to focus more attention on the howquestions relating to cultural tourism research rather than just the what. To this end, authors were asked to concentrate on describing the methods used in their research, rather than the findings. They were also asked to reflect on the advantages and disadvantages of the methods used, and the improvements and developments that could be realized by other researchers.